India - Improving Urban Water Supply and Sanitation Services : Lessons from Business Plans for Maharashtra, Rajasthan, Haryana and International Good Practices - World Bank (Washington, DC, 2012)
The purpose of this report is to distill lessons learnt for improving Water Supply and Sanitation (WSS) services in India, by reference to the recent WSS business plans prepared for the three states of Maharashtra, Rajasthan and Haryana and from various studies carried out by the World Bank on international good practices in urban water service delivery. The report culls out the core elements of the WSS reform program and proposes how such reforms might be implemented. The intended audience for this report is policy makers at the national and state levels, sector professionals and practitioners. The report identifies the key elements of a state-wide program for improving WSS services and accountability on the basis of the following three pillars: i) policies and institutions: appropriate policies and institutional arrangements that clarify the roles and responsibilities of key actors, and which create service providers that are efficient, accountable and customer focused with sufficient autonomy to manage their affairs in a professional manner; ii) infrastructure and financing: medium term infrastructure development program with appropriate financial frameworks that encourage service providers to rely increasingly on user fees and, later on, loans as their main sources of financing. Any subsidies within that framework should be provided in a targeted and transparent manner to support government policies; and iii) capacity building for professional services: ensuring well trained, knowledgeable and motivated staff to deliver the services in a high quality manner. To put the sector in context, the report begins by summarizing the results of various international studies undertaken over the last several years by the World Bank to better understand the makings of well run public WSS companies. These findings point towards the need to establish sectors which encourage the development of autonomous, accountable and customer oriented service providers. Within that framework the report provides suggestions on practical steps that can be taken by governments and service providers.